Designing damping alloys for transport equipment - Akubayeva, Dariya; Zhumagulova, Roza; Zharaspaeva, Gulzhanar; Azhiyeva, Galiya (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is carbon and alloy steels for parts with high surface hardness and increased wear resistance at low deformation. Carbon steels 40, 45, and similar steels with increased manganese content 40G, 45G, 50G are used to manufacture a wide variety of machine parts. Most often, these steels are used for articles that bear the greatest impact loads. Machine parts are exposed to vibration and impact, which results in the generation of intense noise. Noise has a negative impact on human health and reduces performance. One of the ways to solve this problem is to reduce noise by damping it at the source. The results of studies conducted in this area have made it possible to design damping alloys, subject to taking into account the operation of the parts, the percentage of alloying elements, carbon-containing additives, temperature, holding, and not allowing a decrease in the strength properties of the developed alloys. Chromium, manganese, silicon, and nickel were selected as alloying elements for the designed alloys. The chemical composition of the studied carbon alloy steels, average values of sound levels, and sound pressure levels of the studied steels after forging, annealing, and normalization were analyzed. The ADM-1 grade alloy has been proposed for the manufacture of the main transport units (crankshafts, connecting rods, gear rims, passenger car axle shafts, camshafts). Comparison of the acoustic properties (frequency spectrum in octave bands) of the designed steels and known steels with high surface hardness and increased wear resistance after various types of heat treatment has made it possible to identify a pattern. At frequencies of 8000 and 16000 Hz, the designed steels ADM-1, ADM-2, ADM-3 emit noise 6–13 dB lower than similar steels 40, 45, 40G, 45G, 50G